A secure authenticated and key exchange scheme for fog computing. Issue 9 (21st October 2021) - Chen, Chien-Ming; Huang, Yanyu; Wang, King-Hang; Kumari, Saru; Wu, Mu-En
ABSTRACT: Fog computing architecture is used in various environments such as smart manufacturing, vehicular ad hoc networks. However, as an extension of cloud computing, inheriting security challenges of cloud computing is inevitable. Recently, Jia et al. proposed an authenticated key exchange scheme for fog-driven IoT health care systems. Unfortunately, we discovered their scheme is vulnerable to an ephemeral secret leakage attack. In this paper, we propose an authenticated key exchange scheme for fog computing. Compared with previous schemes, our proposed scheme performs better in terms of performance and security.